Metagenomes of Red Sea Subpopulations Challenge the Use of Marker Genes and Morphology to Assess Trichodesmium Diversity - Koedooder, Coco; Landou, Etai; Zhang, Futing; Wang, Siyuan; Basu, Subhajit; Berman-Frank, Ilana; Shaked, Yeala; Rubin-Blum, Maxim (Frontiers in Microbiology, 2022)
Trichodesmium are filamentous cyanobacteria of key interest due to their ability to fix carbon and nitrogen within an oligotrophic marine environment. Their blooms consist of a dynamic assemblage of subpopulations and colony morphologies that are hypothesized to occupy unique niches. Here, we assessed the poorly studied diversity of Trichodesmium in the Red Sea, based on metagenome-assembled genomes (MAGs) and hetR gene-based phylotyping. We assembled four non-redundant MAGs from morphologically distinct Trichodesmium colonies (tufts, dense and thin puffs). T. thiebautii (puffs) and T. erythraeum (tufts) were the dominant species within these morphotypes. While subspecies diversity is present for both T. thiebautii and T. erythraeum, a single T. thiebautii genotype comprised both thin and dense puff morphotypes, and we hypothesize that this phenotypic variation is likely attributed to gene regulation. Additionally, we found the rare non-diazotrophic clade IV and V genotypes, related to T. nobis and T. miru respectively, that likely occurred as single filaments. The hetR gene phylogeny further indicated that the genotype in clade IV could represent the species T. contortum. We show that hetR phylotyping overestimates Trichodesmium diversity, as two copies of the hetR gene were present within T. thiebautii genomes, one of which misidentified this lineage as T. aureum. Taken together, our results highlight the importance of re-assessing Trichodesmium taxonomy while showing the ability of genomics to capture the complex diversity and distribution of Trichodesmium populations.